Psychological hardness and its relation to social interaction The students of the institutes of the ministry of education in the Kurdistan region-Iraq - Diman Abdulstar Jawhar yaba; Muhammad Muhyaddin Sadia Al-Jabbari (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The current study aimed to identify the relationship between psychological hardiness and social interaction among students of the institutes of the Ministry of Education in the Kurdistan Region of Iraq. The level of social interaction according to the variable (sex, academic stage, type of institute), and the study sample consisted of students from the institutes of the Ministry of Education (governmental) for the Kurdistan region in the city of Erbil, who are continuing at all times for the academic year (2021-2022), with the exception of the evening study. The study relied on the descriptive approach in both its relational and comparative parts. the researcher prepared the scale of psychological hardness which consist of (39) items with five alternatives (1,2,3,4,5) and made social interaction scale which consist of (31) items with five alternatives (1,2,3,4,5) as tools for the study. The stability of the psychological hardiness scale reached (0.94) and the social interaction scale was (0.97). The Statistical Package for the Social Sciences (SPSS) was used to process the data. and the results of the study showed that there was a high level of psychological hardness among the study sample. Statistically significant differences in the social relationship according to the variable (sex), followed by the variable (study stage), and based on the results of the study, the researcher recommended conducting more studies to reveal the level of psychological hardness and social interaction and the relationship between them in different age groups and samples.